UNVEILING GENDER OPPRESSION THROUGH INSTITUTIONAL CONTROL OF WOMEN IN IMMACULATE - I Putu Sananda Krisna Artawan; I Gusti Ayu Mahatma Agung; Gek Wulan Novi Utami (Journal of Language and Literature, 2026)
This study aims to analyze gender oppression in the horror film Immaculate directed by Michael Mohan. The study seeks to understand how gender oppression is shown through the main female character's experiences inside a religious institution. Using a qualitative method, this study relied on repeated viewing of the film and examined selected scenes, dialogues, and character interactions that highlight the main character's experiences of oppression. The data was then analyzed through Iris Marion Young's Five Faces of Oppression theory, which provides a useful framework for identifying how oppression works against marginalized individuals. The findings show that all five forms of oppression appear in the film, namely exploitation, marginalization, powerlessness, cultural imperialism, and violence. The main character's body was used by the institution without her knowledge or consent for religious purposes. She was excluded from meaningful participation within the convent community, and she had no power to make decisions about her own body and health. She was also forced to accept the institution's dominant belief system and suffered physical violence as a deliberate means of institutional control. These findings show how Immaculate criticizes gender-based oppression within religious and institutional settings.